2005
DOI: 10.1111/j.1365-294x.2005.02540.x
|View full text |Cite
|
Sign up to set email alerts
|

An interspecific comparison of foraging range and nest density of four bumblebee (Bombus) species

Abstract: Bumblebees are major pollinators of crops and wildflowers in northern temperate regions. Knowledge of their ecology is vital for the design of effective management and conservation strategies but key aspects remain poorly understood. Here we employed microsatellite markers to estimate and compare foraging range and nest density among four UK species: Bombus terrestris, Bombus pascuorum, Bombus lapidarius, and Bombus pratorum. Workers were sampled along a 1.5-km linear transect across arable farmland. Eight or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
379
6
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(396 citation statements)
references
References 44 publications
(72 reference statements)
10
379
6
1
Order By: Relevance
“…The maximum foraging ranges of four UK species of bumblebee (Bombus spp. ), which are one of the main pollinators of wild cherry, are estimated to range from 449 to 758 m (Knight et al, 2005) and recent evidence from radio tracking has showed that bee flight distances are significantly shorter in poor weather conditions (Pasquet et al, 2008). Foraging patterns across this range would account for the long-distance pollination events observed in our study.…”
Section: Discussionsupporting
confidence: 52%
“…The maximum foraging ranges of four UK species of bumblebee (Bombus spp. ), which are one of the main pollinators of wild cherry, are estimated to range from 449 to 758 m (Knight et al, 2005) and recent evidence from radio tracking has showed that bee flight distances are significantly shorter in poor weather conditions (Pasquet et al, 2008). Foraging patterns across this range would account for the long-distance pollination events observed in our study.…”
Section: Discussionsupporting
confidence: 52%
“…proportion of OSR pollen was 10% in average for 475 honeybees as opposed to 32% in average for bumblebees). It may also be because bumblebees tend 476 to forage over shorter distances compared to honeybees (Knight et al, 2005), which may mean that 477 there is less dilution of pesticide residues coming in to the nest when these are located in the vicinity 478 of arable lands. However, it should be noted that our data set is small, and that honeybee hives and 479 bumblebee colonies were not placed in exactly the same localities.…”
Section: Discussion 404mentioning
confidence: 99%
“…Preliminary direct gene-flow estimates from our study site suggest that the majority of pollination events occur between relatively close neighbours. Bumblebees (Bombus spp) are among the major pollinators for wild cherry and the maximum foraging ranges of four UK species have been estimated to range from 449 to 758 m (Knight et al, 2005). However, resource availability is a key factor influencing foraging and individual bees are likely to visit relatively few mature wild cherries before becoming satiated and returning to the nest, thus limiting pollen dispersal.…”
Section: Discussionmentioning
confidence: 99%